THE RELATION OF PERSONAL ANXIOUSNESS AND SELF-AWARENESS ABOUT THE HEALTH CONDITION, AND ITS INFLUENCE ON 16-YEAR RISK OF ACUTE CARDIOVASCULAR DISEASES DEVELOPMENT IN WOMEN 25-64 YEARS OLD - V. V. Gafarov; D. O. Panov; E. A. Gromova; I. V. Gagulin; A. V. Gafarova (Российский кардиологический журнал)
Aim. To evaluate the influence of personal anxiousness (PA) on the relative risk of myocardial infarction and stroke development in the open cohort of women 25-64 years old during 16 years.Material and methods. As a part of MONICA-psychosocial in 1994 the random representative group of women was studied in the age of 25-64 y. (n=870), living in one of the districts of Novosibirsk. PA was assessed by Spielberg test. During 16-year period (1994-2010) in this cohort, all cases of primary myocardial infarction and stroke cases were studied.Results. The prevalence of higher PA in open population among women of 25-64 y.o. was 60%. Higher PA was related to lower self-assessment about health. During 16 years the relative risk of myocardial infarction development was 4.2 (p=0,05), stroke 3.5 (p<0,05) times higher in women with higher PA. The rate of myocardial infarction and stroke development was higher in married women with PA in social frame "senior manager" and "strenuous labour" with higher or lower level of education.Conclusion. The studied prevalence of higher PA risk in open population of 25-64 y.o. women reached 60%. Women with higher PA had higher relative risk of myocardial infarction and stroke during 16 years follow-up, low self-awareness about the health; risk of infarction is related to social gradient.